Self-care needs among international migrants and travellers: A systematic review and meta-synthesis - Antonius Nugraha Widhi Pratama; Brahmaputra Marjadi; Jack Charles Collins; Rebekah Jane Moles; Carl Richard Schneider (PLoS ONE, 2026)
International travellers and migrants perform self-care to maintain their health in their destination countries. The aim of this review was to determine the self-care needs of international travellers and temporary migrants, and to assess how these needs align with existing self-care frameworks. We conducted a systematic review and meta-synthesis, searching MEDLINE, Embase, International Pharmaceutical Abstracts, PsycINFO, and CINAHL for studies on self-care among international travellers or migrants without limiting date and language. Two reviewers performed title and abstract screening after deduplication, followed by full-text screening. Two reviewers used the Center for Evidence-Based Medicine’s (CEBM) Critical Appraisal of Qualitative Studies to assess the quality of selected articles. Discrepancies were resolved by consensus with a third reviewer. Thomas and Harden’s thematic synthesis was applied to synthesise the included literature. El-Osta’s Self-Care Matrix (SCM) was used as a sensitising concept and to map conceptual similarities of descriptive themes. The protocol was registered in PROSPERO (CRD42022372693). The searches retrieved 2,394 articles, of which 17 were considered acceptable quality and included in the meta-synthesis, totalling 769 participants. Two studies were conducted among travellers and 15 among migrants. Twenty-one descriptive themes were generated, and five analytical themes were synthesised. All descriptive themes, except social engagement, were mapped to the SCM, with partial convergences occurring for self-care products and medicines, self-treatment, and treatment adherence. This meta-synthesis identified five self-care needs: self-care empowerment, mutual understanding, healthcare challenges and opportunities, preventive self-care, and self-care facilitation. Travellers’ and migrants’ reduced social capital (resource-gaining from social networks) may impact their ability to self-care, and social engagement is a form of social capital important for their self-care.